Regularização fundiária sustentável urbana e seus instrumentos - Mukai, Sylvio Toshiro (2007)
The goal of the present study is to analyze the sustainable regularization of the illegal occupation of the urban land and its instruments. Initially an effort to concept the term sustainable and its evident connection with the expression Healthy City was made, analyzing its application in Environmental Law and its connection with the elements which form a sustainable city, giving the contours of this concept and its practical application in Urban Law and, consequently, being a defining element in the concretization of the regularization of the illegal occupation of the urban land. Starting from the idea that the right to sustainable cities is enforced by the Constitution, as well as by the Law nº 10.257, from July 10th, 2001, and that it is profoundly connected to the right to have a place to live, which fundaments every action of regularization of the illegal occupation of the land. Under this aspect we analyzed some juridical institutions that can and should be used in the sustainable regularization of the illegal occupation of urban land. In this context, the study still focused another important theme: the law proposal which is in progress at the Congress and which brings other juridical contours to the sustainable regularization of the illegal occupation of urban land, besides those laws contained in bills already established. Obviously the intended regularization cannot be tied to instruments which target simply the juridical security of the institute of possession. The sustainability intrinsic to this regularization imposes the necessity of using the other juridical instruments, as well as of other actions that can make the regularization of the illegal occupation of the urban land effectively sustainable. It is necessary to remember, although, that only the effective application of an inclusive urban policy will make the sustainability of this intended regularization possible. This is the conclusion of this study